GAP Analysis of Higher Education Quality Assurance System Implementation Against Educational Organization Management Standards ISO 21001:2018 - Yudi Syahrullah; April Yanti; Tigar Putri Adhiana; Rani Aulia Imran (Universitas Mercu Buana, 2022)
ISO 21001:2018 is an international standard for the management system of educational organizations that formal education organizations can apply to achieve their goals and functions to provide quality educational services. Currently, there are study programs with C accreditation and 2 study programs accredited B at Faculty of X under The University of Y. Hence, quality assurance at Faculty X still needs to be improved to achieve the highest accreditation. It is hoped that an education management system that refers to the ISO 21001:2018 standard can assist organizations in meeting these goals and targets. Faculty X has not implemented the ISO 21001:2018 quality assurance system but has implemented a quality assurance system through an internal academic quality audit process known as AIMA. This study aims to determine the GAP between the current higher education quality assurance system and the educational organization management system ISO 21001:2018 and determine the level of readiness obtained by Faculty X to meet the requirements of ISO 21001:2018. The results show that 59% of the ISO 21001:2018 clauses have been completed in the higher education quality assurance standard based on AIMA (Academic Quality Internal Audit Instrument), and 41% of the requirements still do not meet the AIMA standard. The percentage of readiness obtained by Faculty X in implementing the management system of educational organizations ISO 21001:2018 is 73%, which means that Faculty X still has to improve the quality system in preparation for ISO 2100:2018 quality assurance. Improvements in meeting the ISO 21001:2018 educational organization management system are plans for consistent improvement, monitoring, and evaluation.